THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, LEARNING INDEPENDENCE, AND LEARNING FACILITIES AT HOME WITH MATHEMATICS LEARNING OUTCOMES - Mega Ellimas Miranti; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Mathematics learning outcomes of students correlate with many factors. Numerical ability, learning independence, and learning facilities at home are considered to correlate with learning outcomes. The purpose of this research is to know that there is a positive and significant correlation between numerical ability, learning independence, and learning facilities at home with mathematics learning outcomes for students from class VIII at State Junior High School (SMP Negeri) 4 Yogyakarta first semester in 2017/2018 school year. This research population comprises students from class VIII in the first semester at SMP Negeri 4 Yogyakarta in the 2017/2018 school year, consisting of 5 classes with 169 students. The sample is taken with random technique sampling toward class, and class VIII C consisted of 33 students. The data collection technique uses the questionnaire technique and test. Research instrumental test uses validity, reliability, and T-test. Prerequisite analysis test involves normality, independent, and linearity test. Data analysis uses correlation and regresses linear analysis. The result of this research shows that there is positive and significant correlation between numerical ability (X1), learning independency (X2), and learning facilities at home (X3) with mathematics learning outcomes of students with Fount > Ftable is 5,320 > 2,93 with R = 0,596 and R2 = 0,355 with and SR(X1) = 46,856 %, RC (X2)= 18,545 %, and RC (X3)= 34,599 %, EC (X1) = 16,633 %, EC (X2) = 6,583 %, and EC (X3)= 12,282 %.